Analysis of the humanitarian logistics network for the colombian coffee zone (quindío department) (Revista Cientifica Ingenio Magno, 2022)
In order to address different situations that affect the physical and mental wellbeingof people caused by different natural disasters that may occur due to unavoidablephenomena or climate change, identifies the humanitarian logistics network for thedepartment of Quindío, Colombia for further analysis and interpretation. The mixed researchmethodology is used in order to understand the problems, population under study andinvolved within the logistics network for the development of the graph. By configuring thenumber of actors and networks identified, the analysis is done by communities that allows usto know the deficiencies of the department at the time of responding to a natural disaster;thanks to this I can identify the lack of coordination between actors and the low density ineach of the networks that generates an obvious problem due to the importance of each one.
Keywords: Humanitarian logistics; natural disaster; humanitarian aid; graph theory; logistics network.